International declaration of parentage before the Supreme Court. Supreme Court case Law Nº 223 and 224, 17th April 2018 - Guzmán Zapater, Mónica (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
In two cases Spanish Supreme Court goes through the question of temporary application of new rules on jurisdiction and applicable law in ascertainment filiation actions. Taking into account interest and values on filiation actions finally establishes ad hoc solutions in each case avoiding a formal declaration on it´s retroactive consequences.
Keywords: filiation; international jurisdiction; applicable law; time element in conflict of law rules; values and objectives; other questions